Short-Term Seismic Precursor Anomalies of Hydrogen Concentration in Luojishan Hot Spring Bubbling Gas, Eastern Tibetan Plateau - Zhou, Xiaocheng; Yan, Yucong; Fang, Wenya; Wang, Wanli; Shi, Hongyu; Li, Pengfei (Frontiers in Earth Science, 2021)
The gas compositions (He, H2, CO2, N2, Ar, and CH4) and isotope ratios (3He/4He and δ13C) were yearly investigated from April 2010 to April 2019 at the Luojishan spring in the Zemuhe fault, eastern of the Tibetan Plateau. The continual automatic monitoring of hydrogen in Luojishan hot spring bubbling gas for the purpose of earthquake prediction requires the discrimination of seismic precursor anomalies from seismically-induced anomalies. The data showed (1) Helium isotope ratios (3He/4He) in hot springs bubbling gas varied from 0.05 to 0.17 Ra (Ra=air 3He/4He=1.39×10-6), with Hemantle-derivd up to 2.2 % in the Luojishan hot spring (assuming R/Ra=8 for mantle) indicated the ZMHF was a conduit for dominant crust-derived fluid. N2 concentrations of the majority of hot spring gas samples were ≥80 vol.%, and δ13CCO2 values varied from −13.2‰ to −9.3‰ (vs.PDB). (2) The time series of hydrogen display a complex temporal pattern reflecting a wide range of different physical processes. There were obviously short-term (5~60 h) seismic precursor anomalies of hydrogen concentration related with the epicentral distance and magnitude of earthquake before natural earthquake, with post-seismic response. The artificial earthquake only induced the post-earthquake responses. Monitoring of automatic hydrogen concentrations stations may be a promising tool for unraveling short term seismic precursor mechanisms and for earthquake prediction.